Efficacy of ondansetron as antiemetic agent in preventing the incidence of PONV in LSCS under subarachnoid block - P.T., Shivanand; J, Vasantha Kumar; R, Ravi (International Journal of Research in Medical Sciences, 2017)
Background: Nausea and vomiting are the most common distressing symptom in the postoperative period. Antiemetic drugs play an important role in therapy of PONV. Though many drugs have been tried as prophylaxis and treatment of PONV, no drug has been proved significantly effective and hence, the present study was undertaken to evaluate the efficacy of prophylactic ondansetron in LSCS patients given spinal anaesthesia. Methods: After institutional approval and informed consent 100 ASA I & II patients undergoing non emergent LSCS taken for study. The patients were received ondansetron 4mg i.v. 3-5min before surgery. Episodes and severity of nausea, vomiting and retching were noted at the end of 1st, 2nd, 6th and 24th hr. Results: The mean age, weight and duration of surgery was not significantly different when compared group-A parturiants with group-B. The mean episodes of emesis, nausea and retching at different postoperative duration were significantly decreasing as postoperative time progresses. Conclusion: The present study suggests that prophylactic ondansetron 4mg is more efficacious in preventing post operative nausea and vomiting in LSCS under spinal anaesthesia.